Neuromyelitis optica spectrum disorders may be misdiagnosed as Wernicke's encephalopathy. (2nd October 2016) - Shan, Fulan; Zhong, Rong; Wu, Linzhan; Fan, Yongxiang; Long, Youming; Gao, Cong
Abstract : Purpose: To raise doctors' attention to the differential diagnosis of neuromyelitis optica spectrum disorders (NMOSD) and Wernicke's encephalopathy (WE). Patients and methods: We extensively reviewed the medical records of 136 patients who had visited our hospital since 2008 and were suspected of having central nervous system demyelinating diseases. Four of those patients had somnolence, electrolyte imbalance and brain lesions around the third ventricle and were included in the study. We tested the serum of the four patients for the presence of aquaporin-4 (AQP4) M23 antibody. Results: All the four patients had positive AQP4 antibody in their serum. Two of the patients were misdiagnosed as WE before AQP4 antibody detection occurred. Conclusions: NMOSD and WE have similar brain lesion locations, histopathological changes and clinical manifestations. It is important to distinguish NMOSD from WE by detecting AQP4 antibody in serum or cerebral spinal fluid. Vitamin B1 should also be administered to the patients who have a history of thiamine deficiency.